2023
DOI: 10.1186/s40537-023-00703-w
|View full text |Cite
|
Sign up to set email alerts
|

Data-centric artificial intelligence in oncology: a systematic review assessing data quality in machine learning models for head and neck cancer

Abstract: Machine learning models have been increasingly considered to model head and neck cancer outcomes for improved screening, diagnosis, treatment, and prognostication of the disease. As the concept of data-centric artificial intelligence is still incipient in healthcare systems, little is known about the data quality of the models proposed for clinical utility. This is important as it supports the generalizability of the models and data standardization. Therefore, this study overviews the quality of structured and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 184 publications
0
8
0
Order By: Relevance
“…Due to the moderate number of included patients and the different primary tumor site distributions between the OUS and MAASTRO datasets ( Table 1 ), a mixed analysis, i.e., including all primary tumor sites in the datasets, was preferred over subgroup analysis, i.e., focusing on one single primary tumor site. Mixed analysis for HNC outcome prediction is also encountered frequently in the literature, as summarized in Adeoye et al ( 37 ).…”
Section: Methodsmentioning
confidence: 99%
“…Due to the moderate number of included patients and the different primary tumor site distributions between the OUS and MAASTRO datasets ( Table 1 ), a mixed analysis, i.e., including all primary tumor sites in the datasets, was preferred over subgroup analysis, i.e., focusing on one single primary tumor site. Mixed analysis for HNC outcome prediction is also encountered frequently in the literature, as summarized in Adeoye et al ( 37 ).…”
Section: Methodsmentioning
confidence: 99%
“…Noise in label assignment can originate from insufficient information, subjectivity, and coding issues. Regarding classes parity, a recent systematic review on data quality in AI models for head and neck cancer [19] suggested that models with good balance in the outcome classes had significantly higher median discrimination than those that did not adjust for classes imbalance.…”
Section: Type and Quality Of Datamentioning
confidence: 99%
“…A review published in 2022 also indicated that among the AI-related studies focused on the head and neck, the number of investigations with the use of external validation in the test session is relatively small. 122 For an appropriate external-validation procedure, the use of large amounts of data from public academic institutions (e.g., J-MID from the Japan Radiology Society) may be one of the steps to solve this problem. 123 Further research is necessary to address these limitations, as are discussions to integrate the existing knowledge and future aspects.…”
Section: Future Perspectivementioning
confidence: 99%